Numerical analysis of hydrodynamic characteristics and interphase coupling in a gas‐solid cyclone reactor. (21st April 2021) - Li, Anjun; Wang, Zhenbo; Zhu, Liyun; Wang, Ziyi; Xu, Xiaogang; Fang, Liang
Abstract: A down‐flow gas‐solid cyclone reactor (GSCR) for fluidized catalytic cracking process was proposed to solve the side reactions. Comprehensive three‐dimensional numerical models were established to interpret its gas‐solid flow features, where the continuous phase and dispersed phase were modelled in the Eulerian grid and Lagrangian framework, respectively. Simulation results show that the four‐way approach has a better prediction of gas‐solid flow hydrodynamics in GSCR than the two‐way approach, and the numerical pressure drop agreed well with the experimental data. Most catalysts accumulated on the wall when descending and the phase interface structure composed of internal pure gas and external mixtures was subsequently formed. The radial distribution of tangential velocity was almost hump shaped. Tangential and axial kinetic energies accounted for 92.49%–95.45% of total kinetic energy and were thus dominant. In the dilute condition, the oscillatory behaviour of particle concentration was more severe than that of gas velocities, and particle concentration and gas tangential velocity had the same dominant frequency (~2.6 Hz). As the particulate loading increased tenfold, the hydrodynamic characteristics became rather complex.